Implementation Of Diabetic Foot Spa And Sauna Bathing On Quality Of Sleep And Blood Glucose Levels In Individuals With Type 2 Diabetes - Nur Ainiyah; Erika Martining Wardani (Universitas Nahdlatul Ulama Surabaya, 2021)
Background: Diabetes is a chronic disease of glucose metabolism, which causes blood circulation obstruction such as tingling and leg pain, and itching. This study aims to determine the effect of diabetic foot spa and sauna bathing on sleep quality and blood glucose levels in individuals with type 2 diabetes. Methods: The design used a quasi-experimental. This study's population was all individuals with type 2 diabetes, applied simple random sampling, and a sample size of 60 respondents. The inclusion criteria were individuals with type 2 diabetes who did not have complications. The independent variables were sleep quality and blood glucose levels. The dependent variables were diabetic foot spa and sauna bathing. The instrument used a Pittsburgh Sleep Quality Index (PQSI) and a glucometer. The data analysis test utilized the paired t-test and independent t-test with a p-value of 0.000 (p <0.005). Results: The results of this study showed that 60 respondents, mostly (70%) women, 58.3% were aged 45- 60 years, almost half of the respondents (48.3%) had diabetes for less than one year up to five years and from the results t-test obtained p=0.000 (p <0.05). Conclusion: There was an effect of diabetic foot spa and sauna bathing on sleep quality and blood glucose levels